Vitamin D status in Thai dermatologists and working-age Thai population - Natta Rajatanavin (2020)
© 2018 Japanese Dermatological Association This study aimed to determine the prevalence of vitamin D insufficiency among Thai dermatologists compared with the general working-age population in Bangkok. A cross-sectional study was conducted in healthy Thai physicians who had at least 1 years’ experience in dermatology practise and a subsample of the general Thai population from the Fourth National Health Survey. Serum 25-hydroxyvitamin D (25[OH]D), a combination of 25(OH)D2 and 25(OH)D3, levels in both groups were measured using liquid chromatography coupled with mass spectrometry. The majority of dermatologists were of Fitzpatrick skin type III (n = 61, 61.3%) or IV (n = 32, 33.3%). The mean serum 25(OH)D and 25(OH)D3 levels were 18.9 and 18.2 ng/mL, respectively, whereas the corresponding levels in the general population were 26.5 and 25.8 ng/mL. None of the dermatologist had serum 25(OH)D sufficiency (>30 ng/mL), 38 (38.78%) had vitamin D insufficiency (20–30 ng/mL) and 60 (61.22%) had vitamin D deficiency (<20 ng/mL). The frequency of vitamin D deficiency in dermatologists was significantly higher than in the general population (61.2% vs 19.2%, P < 0.001). Ninety percent of dermatologists used sunscreen daily and spent time mostly indoors. Dermatologists used physical sun-protection more than half of the time when outdoors, for example, a book or paper as a sunshade (70.3%), an umbrella (48.4%), a long-sleeved shirt (20.4%) or a hat (9.7%). In conclusion, dermatologists showed a remarkably high prevalence of vitamin D deficiency which may be due to inadequate exposure to sunlight, regular use of sunscreen and practicing various sun-protection activities.